Theoretical and legal issues of forensic psychological examination - Izbassova А.Б.; Malikova Ш.Б.; Kan А.Г. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The article is devoted to theoretical and legal issues of forensic psychological examination and issues of legislative regulation in the Republic of Kazakhstan. Forensic psychological examination is the main form of attracting psychologists to legal practice. The appeal to them by representatives of investigative bodies has both objective and subjective reasons. Firstly, the data of the forensic psychological examination are one of the sources of evidence and serve to establish the truth. On the other hand, the availability of expert data gives the investigator confidence in solving the issue, allowing to reduce the likelihood of making a mistake. The purpose of the article is to analyze some theoretical, legal, organizational issues of conducting forensic psychological examination in criminal proceedings and take it as a basis for developing recommendations for improving the conduct of criminal proceedings in the Republic of Kazakhstan. One of the main issues was considered the concept, essence, subject and objects of forensic psychological examination and formulated the legal basis for the appointment of forensic psychological examination in criminal proceedings. In the criminal proceedings of the Republic of Kazakhstan, there are significant differences in the definition of methodological properties and characteristics of forensic psychological examination. The normative-technical and psychological-technical requirements developed in the theory of criminal law cannot be useful without a clear practical implementation of the requirements specified in the adopted normative legal acts.